Parasitic encounters in debt: The UK mainstream credit industry. (April 2015) - Walker, Carl; Hanna, Paul; Cunningham, Liz; Ambrose, Peter
Part of making visible the complex of institutions and practices that create and make knowable experiences of debt-related distress is to focus on the classed nature of these experiences. Contemporary bureaucracies of debt and distress need to be understood as reproducing divisions of status, power, and access to resources. The imposition of precarious forms of wage labour for those trapped at the bottom of what is an increasingly polarizing class structure has been shaped by very specific sets of financial practices where a deregulated personal debt industry has integrated subordinate classes into a web of financial relations through private pensions, consumer credit, and mortgages. This article draws upon empirical research with a range of stakeholders in the UK mainstream credit industry. We contend that the institutional logics, discourses, myths, and operational processes of the variety of agencies and actors in the UK mainstream credit sector have, through the radical changes of financial liberalization, evolved into a functional industry. This industry serves to enable, support, and enact social relational and economic practices that can best be understood through the metaphor of parasitism. This paper explores the specific organizational and relational practices that allow the financial exploitation of a beleaguered precariat.